2015
DOI: 10.1504/ijeb.2015.069104
|View full text |Cite
|
Sign up to set email alerts
|

Individual level culture influence on online consumer iTrust aspects towards purchase intention across cultures: A S-O-R model

Abstract: Building trust and understanding its relationship with online purchasing decisions is important to business-to-consumer (B2C) e-commerce firms seeking to extend their consumers reach globally. Based on the StimulusOrganism-Response (S-O-R) model, this paper examines the moderating role of culture on the relationship between B2C web design (web accessibility, visual appearance and social networking services (SNS)) and interpersonal trust (iTrust), cognitive and affect-based trust that trigger online purchasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…Similarly, practitioners of e-commerce, having seen this model and the analyses, would be able to gauge them the preferred motivating construct that has a higher tendency to trigger shoppers' intention to accept a system (Internet shopping). In as much as the success of online businesses relied heavily upon its ability to attract customers, practitioners should improve their systems to provide pre-purchase and post-purchase information to both experienced and inexperienced shoppers [60][61][62].…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, practitioners of e-commerce, having seen this model and the analyses, would be able to gauge them the preferred motivating construct that has a higher tendency to trigger shoppers' intention to accept a system (Internet shopping). In as much as the success of online businesses relied heavily upon its ability to attract customers, practitioners should improve their systems to provide pre-purchase and post-purchase information to both experienced and inexperienced shoppers [60][61][62].…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…Concerning the theoretical relevance, our research whilst contributing to a growing body of work on online shopping behaviour offers a diverse perspective on the motivator factors that trigger the usage and adoption of Internet shopping. Previous research has declined the inclusion of some important extraneous variables like government support infrastructure as a composite function of policy stimulus towards response (intent) to used online retail stores [62]. Additionally, with the continuous growth of Internet use and adoption, a review of Internet shopping specific concepts or factors (stimuli) would offer a better explanation of online shopping adoption and usage in the retailing environment.…”
Section: Discussion and Research Implicationsmentioning
confidence: 99%
“…In this study, subjective norm is modelled as a formative construct [27] while all other constructs are modelled as reflective indicators. The subjective norm is a multidimensional construct [59] which covers various referent groups such as friends, family and colleagues.…”
Section: Methodsmentioning
confidence: 99%
“…Within the context of e‐commerce, the S‐O‐R paradigm has shown that different stimuli (website design elements) in the online shopping context can produce diverse consumers’ cognitive, affective, and conative outcomes (arousal, satisfaction, purchase intention, and revisit intention) while performing purchasing tasks (Sohaib & Kang, ). For instance, in a Business to Consumer context, Sohaib and Kang () demonstrated that web‐design elements of shopping websites can have different shopping outcomes across cultures (individualistic vs. collectivistic cultures such as Australia vs. Pakistan) as well as within a culture (Australia). Consistent with the existing studies, this study developed a research model based on the S‐O‐R paradigm.…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%